1993
DOI: 10.1590/s0034-89101993000500004
|View full text |Cite
|
Sign up to set email alerts
|

The social adjustment of patients with schizophrenia: implications to the mental health policy in Brazil

Abstract: A sample (n=124) of schizophrenic patients from a defined catchment area of the city os S.Paulo, Brazil, who had been consecutively admitted to hospital, was assessed for psychopathological status and social adjustment levels. Sociodemographic, socio-economic and occupational characteristics were recorded: almost 30% of the subjects had no occupation and received no social benefit, more than two-thirds had a monthly per capita income of US$ 100.00 or less. Sixty-five percent presented with Schneiderian firstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
4

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
1
9
1
4
Order By: Relevance
“…17 As in their study, social withdrawal and participation in household activities were the items in which patients presented higher levels of disability, but, differently from that, in the present study, the item where most patients showed any degree of dysfunction was underactivity. The item where fewer subjects were reported to have any level of disability was social contacts, a finding similar to that of Menezes and Mann.…”
Section: Interpretation Of Resultscontrasting
confidence: 70%
“…17 As in their study, social withdrawal and participation in household activities were the items in which patients presented higher levels of disability, but, differently from that, in the present study, the item where most patients showed any degree of dysfunction was underactivity. The item where fewer subjects were reported to have any level of disability was social contacts, a finding similar to that of Menezes and Mann.…”
Section: Interpretation Of Resultscontrasting
confidence: 70%
“…14 In many societies in low and middle income countries, most individuals with severe mental illnesses live with and rely upon their families to survive. 13,19 This may decrease their exposure and 19 reinforcing this assumption. In Brazil, smoking is allowed in most psychiatric hospitals, and it is common the use of cigarettes to maintain patients calm and under control, given as a reward for "good behavior" in the ward.…”
Section: Discussionmentioning
confidence: 80%
“…The authors argued that lack of fi nancial independence might explain such fi nding, through restrictions imposed by the families of those with severe mental illnesses. In Brazil, high fi nancial dependence is also common among people with severe mental illnesses, 13 and the prevalence of substance misuse among them is much lower than that observed in developed countries. 14 Therefore, the prevalence of cigarette smoking people with severe mental illnesses may not follow the pattern seen in developed countries.…”
Section: Descritores: Pessoas Mentalmente Doentes Diagnóstico Duplo mentioning
confidence: 98%
“…Estes encontraram 0,6% de demanda potencial de tratamento para o paciente psicótico na população geral 8 , que 30,0% desses são graves e demandam hospitalizações repetidas 9 . Dentre os hospitalizados, 50,0% são internados novamente caso não sejam tratados adequadamente na comunidade 10 . Baseado neste cenário, estimamos que 416 pacientes necessitariam de hospitalização na Cidade de Santos, caso não estivessem encontrando tratamento adequado na comunidade.…”
Section: Discussionunclassified